Inhalable Protein Powder Prepared by Spray-Freeze-Drying Using Hydroxypropyl-β-Cyclodextrin as Excipient - Jason C. K. Lo; Harry W. Pan; Jenny K. W. Lam (MDPI AG, 2021)
The prospect of inhaled biologics has garnered particular interest given the benefits of the pulmonary route of administration. Pertinent considerations in producing inhalable dry powders containing biological medicines relate to aerosol performance and protein stability. Spray-freeze-drying (SFD) has emerged as an established method to generate microparticles that can potentially be deposited in the lungs. Here, the SFD conditions and formulation composition were evaluated using bovine serum albumin (BSA) as a model protein and 2-hydroxypropyl-beta-cyclodextrin (HPβCD) as the protein stabilizer. A factorial design analysis was performed to investigate the effects of BSA content, solute concentration of feed solution, and atomization gas flow rate on dispersibility (as an emitted fraction), respirability (as fine particle fraction), particle size, and level of protein aggregation. The atomization gas flow rate was identified as a significant factor in influencing the aerosol performance of the powder formulations and protein aggregation. Nonetheless, high atomization gas flow rate induced aggregation, highlighting the need to further optimize the formulation. Of note, all the formulations exhibited excellent dispersibility, while no fragmentation of BSA occurred, indicating the feasibility of SFD and the promise of HPβCD as an excipient.